Product Ecodesign in Slovenia’s ISO 14001-Certified Manufacturing Companies - Radonjič, Gregor; Pisnik Korda, Aleksandra (Naše gospodarstvo/Our economy, 2012)
The manufacturing and use of products have extreme impacts on the natural environment and the depletion of natural resources. Product ecodesign principles are based on the idea of the inclusion of environmental aspects of a product over its entire environmental lifecycle. The aim of the study was to gather and evaluate situations on ecodesign in ISO 14001-certified manufacturing companies in the Republic of Slovenia in order to investigate whether product ecodesign measures are promoted as a result of adopting ISO 14001 certification or not. The most important ecodesign criteria were evaluated and prioritized. In addition, the main drivers and barriers as well as information sources on product ecodesign were determined.
Keywords: ISO 14001; products; ecodesign; eco-innovations; environmental management system